(untitled) (Research in Agriculture Livestock and Fisheries, 2019)
The study was conducted to assess the profitability of Khirshapati variety mango cultivation and to analyze factors affecting productivity of this variety in four districts namely Khagrachori, Bandorban, Naogaon, and Satkhira of Bangladesh during February to March, 2018. Data were collected from 72 mango orchards using random sampling method. Descriptive statistics, profitability analysis and Cobb-Douglas type production function was used to analyze data. The per hectare gross cost, gross return and net return were Tk. 507817,Tk. 72,8419 and Tk. 22,0602 respectively for the 6-7 years of Khirshapati mango orchard. Net present value was Tk. 65,343 and benefit cost ratio was 1.16 which ensures that investment in mango cultivation is financially feasible. Mango cultivation was also found to be a profitable enterprise since internal rate of return was 20%.The functional analysis indicates that per hectare yield were significantly positively influenced by age of the orchard, number of tress and amount of fertilizer. The results also show that area and amount of manure had significant negative effects. So a proper initiative should be taken to disseminate this information among the mango growers to sustain the yield of Khirshapati mango in Bangladesh. Res. Agric., Livest. Fish.6(1): 35-43, April 2019